2023
DOI: 10.3389/fcvm.2023.1173363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acupressure on pain level and hemodynamic parameters after coronary angiography: a randomized controlled study

Abstract: BackgroundSubsequent to coronary angiography, procedures performed to prevent bleeding may cause pain in the patient. In this study, we aimed to determine the effect of acupressure on pain level and hemodynamic parameters in patients undergoing coronary angiography.MethodIn this prospective, a two-arm (1:1), randomized controlled trial was conducted, with 124 patients undergoing coronary angiography included. The randomly assigned study group (n = 62) received acupressure on the LI4 (on the dorsum of the hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Pain during ESWL increases the risk of kidney hematoma with increased blood pressure [ 7 ]. Our study revealed significant effects of acupressure on patients' systolic blood pressure during the peak of shockwave energy, which is not consistent with the study of Düzel et al [ 34 ]. Khoram et al also found that massaging three points, HT7, EX-HN3, and GB20, effectively reduced anxiety, heart rate, and systolic blood pressure in patients before open-heart surgery [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Pain during ESWL increases the risk of kidney hematoma with increased blood pressure [ 7 ]. Our study revealed significant effects of acupressure on patients' systolic blood pressure during the peak of shockwave energy, which is not consistent with the study of Düzel et al [ 34 ]. Khoram et al also found that massaging three points, HT7, EX-HN3, and GB20, effectively reduced anxiety, heart rate, and systolic blood pressure in patients before open-heart surgery [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Şolt Kirca et al showed that the pain-relieving effects of acupressure at points LV4 and LI4 last for about 120 min [ 16 ]. Corresponding to these findings, Düzel et al (2023) reported beneficial effects in reducing pain in patients after angiography [ 34 ]. However, one study did not find a significant effect of acupressure on the pain of colic patients [ 11 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations